Processual Business: a brief analysis on the aspects (Research, Society and Development, 2021)
With the advent of the Civil Procedure Code 2015, several provisions have emerged with the intention of authorizing the parties to enter into procedural conventions with each other that bind all members of a procedural relationship. Among them, article 190 stands out, which establishes in its wording that, in the case of available rights, the parties may agree on procedural issues, burdens, powers, faculties and procedural duties, before or during the process, subject to the control of validity of the judge and binding all those involved in the procedural relationship. The objective of this work is to carry out an analysis of typical and atypical procedural businesses, their appropriateness and rules. The methodology used was the bibliographic analysis of current doctrine and legislation on the subject. After conducting the survey, we can realize that it is understood that the legislator's intention, when creating such a device, was to honor the principle of autonomy of the parties' will, in order to achieve the main objective of a judicial demand, which is to protect the rights of the parties seeking the judiciary, to the detriment of religious proceduralism. However, the celebration of procedural transactions, especially atypical, must be accompanied with great care, considering that these do not have explicit rules.